Sensitivitas Bakteri Gram Negatif yang Diisolasi dari Kaki Kecoa (Periplaneta americana)di Area Rumah Sakit dan Perumahan di Kota Palu terhadapBeberapa Antibiotik - I Nengah Kundera; Mursito Bialangi (Universitas Sebelas Maret, 2018)
Cockroaches (Periplaneta americana) are often found in homes, restaurants, hotels, hospitals, warehouses, offices, libraries, and others. The existence of these highly dynamic animals is suspected of causing nosocomial infections at the hospitals and acting as vectors and hosts associated with bacteria carried on its feet. This research aims to analyze the sensitivity of Gram-negative bacteria isolated from Cockroach feet in the hospital and residential areas in Palu City against some antibiotics. This research is an explorative laboratory experiment research, with the method of bacteria identification, isolation and antibiotic test using standard procedure